2011
DOI: 10.2112/jcoastres-d-11-00050.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind Speed and Direction on Summer Tidal Circulation and Vertical Mixing in Hong Kong Waters

Abstract: KUANG, C.P.; LEE, J.H.W.; HARRISON, P.J., and YIN, K.D., 2011. Effect of wind speed and direction on summer tidal circulation and vertical mixing in Hong Kong Waters. Journal of Coastal Research, 27(6A), 74-86. West Palm Beach (Florida), ISSN 0749-0208.In subtropical coastal waters around Hong Kong, a well-mixed water body is usually observed after typhoons or strong easterly wind events in summer. A calibrated three-dimensional (3-D) hydrodynamic model for the Pearl River Estuary (Delft3D) was applied to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A stronger ASM leads to intensification of wind-induced upwelling, which, subsequently, decreases the coastal SSTs of northern SCS (e.g. Kong et al, 2015; Kuang et al, 2011; Liu et al, 2013). Moreover, an enhanced upwelling also promotes vertical mixing of nutrient-rich subsurface waters that allows favorable conditions for haptophyte production (Villanueva et al, 1998) and would thereby explain higher C 37 concentrations (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A stronger ASM leads to intensification of wind-induced upwelling, which, subsequently, decreases the coastal SSTs of northern SCS (e.g. Kong et al, 2015; Kuang et al, 2011; Liu et al, 2013). Moreover, an enhanced upwelling also promotes vertical mixing of nutrient-rich subsurface waters that allows favorable conditions for haptophyte production (Villanueva et al, 1998) and would thereby explain higher C 37 concentrations (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, 2017; Jiang and Wang, 2018; Jing et al, 2009; Kong et al, 2015). Furthermore, investigations of three nearby cores in the Mirs Bay (Kong et al, 2015) have indicated that regional SST variations over the past four centuries, as mainly controlled by changes in coastal upwelling, are able to reflect the ASM intensity (Kuang et al, 2011; Liu et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…(2) PR: a high level of PR increases the surface water flow into the estuary area, representing an important source for sediment and nutrient contents [62,63]. (3) WS: the WS not only affects the water surface flow and sediments but also affects the strength of the ocean currents near the estuary area [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Sigma coordinate is used for vertical grid in 3-D simulations. Delft3D FLOW is widely used in the coastal hydrodynamic research (Jiao, 2014;Kuang et al, 2016;Wang et al, 2017b). The wave model for the study is the module WAVE of Delft3D.…”
Section: Modelmentioning
confidence: 99%